Immunomodulatory mechanisms of abatacept: A therapeutic strategy for COVID-19 - Yang, Dinglong; Li, Hetong; Chen, Yujing; Ren, Weiping; Dong, Mingjie; Li, Chunjiang; Jiao, Qiang (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) caused by coronavirus-2 (SARS-CoV-2) infection has rapidly spread throughout the world and become a major threat to human beings. Cytokine storm is a major cause of death in severe patients. Abatacept can suppress cytokines used as antirheumatic drugs in clinical application. This study analyzed the molecular mechanisms of abatacept treatment for COVID-19. Differentially expressed genes (DEGs) were identified by analyzing expression profiling of abatacept treatment for rheumatoid arthritis (RA) patients and SARS-CoV-2 infection patients. We found that 59 DEGs were upregulated in COVID-19 patients and downregulated following abatacept treatment. Gene set enrichment analysis (GSEA) and Gene ontology (GO) analysis showed that immune and inflammatory responses were potential regulatory mechanism. Moreover, we verified 8 targeting genes and identified 15 potential drugs candidates for the treatment of COVID-19. Our study illustrated abatacept could be a promising property to preventing severe COVID-19, and we predicted alternatively potential drugs for the treatment of SARS-CoV-2 infection.